2017
DOI: 10.1007/s00253-017-8432-0
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptome analysis of the thermotolerant yeast Kluyveromyces marxianus CCT 7735 under ethanol stress

Abstract: The thermotolerant yeast Kluyveromyces marxianus displays a potential to be used for ethanol production from both whey and lignocellulosic biomass at elevated temperatures, which is highly alluring to reduce the cost of the bioprocess. Nevertheless, contrary to Saccharomyces cerevisiae, K. marxianus cannot tolerate high ethanol concentrations. We report the transcriptional profile alterations in K. marxianus under ethanol stress in order to gain insights about mechanisms involved with ethanol response. Time-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 42 publications
4
36
1
Order By: Relevance
“…Our results suggested that this fraction was even smaller for Z. meyerae and P. burtonii because of their very low consumption of valine, leucine and phenylalanine and comparatively high production of the corresponding higher alcohols (Table 1 ), while it remained similar for K. marxianus , except for the phenylalanine/phenylethanol ratio which seemed to be higher. Since phenylethanol may be produced through the degradation of compounds arising from the pentose phosphate pathway, this observation is in accordance with the transcriptomic results reported in Diniz et al ( 2017 ). Indeed, the latter authors showed that the genes involved in the pentose phosphate pathway seemed to be overexpressed in the presence of 6% of ethanol.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results suggested that this fraction was even smaller for Z. meyerae and P. burtonii because of their very low consumption of valine, leucine and phenylalanine and comparatively high production of the corresponding higher alcohols (Table 1 ), while it remained similar for K. marxianus , except for the phenylalanine/phenylethanol ratio which seemed to be higher. Since phenylethanol may be produced through the degradation of compounds arising from the pentose phosphate pathway, this observation is in accordance with the transcriptomic results reported in Diniz et al ( 2017 ). Indeed, the latter authors showed that the genes involved in the pentose phosphate pathway seemed to be overexpressed in the presence of 6% of ethanol.…”
Section: Discussionsupporting
confidence: 92%
“…The decline and premature death of K. marxianus during the sequential fermentation could be explained by its difficulty to overcome the ethanol increase and the impact on its plasmic membrane. Indeed, Diniz et al ( 2017 ) demonstrated that the expression of some gene-encoding enzymes related to unsaturated fatty acid and ergosterol biosynthesis decreased upon ethanol exposure, and free fatty acid and ergosterol measurements demonstrate that their content in K. marxianus did not change under this stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of unconventional thermotolerant yeast K. marxianus, however, there were only several reports of transcriptome analysis on yeast responses from different carbon source including glucose, inulin and xylose, or the tolerance to high temperature or ethanol stress. 18,69,70,71 To the best of our knowledge, genome-wide transcription analysis under the multiple inhibitors stress condition with elevated temperature (42 C) has not been reported for this yeast.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that probiotic lactic acid bacteria may change their probiotic capacity when grown on different substrates (10). Furthermore, extensive transcriptomic changes have been described for K. marxianus under 6% ethanol stress (25). Even if this was not the aim of the referenced work, it can be speculated that these transcriptomic changes could affect probiotic features of ethanol-stressed yeasts.…”
Section: Discussionmentioning
confidence: 99%